(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
canis , M. audouinii and M. ferrugineum are three species ofArthroderma otae com- plex, which morphologically and genetically closely related. Conventional identification of phenotypic and biochemical characteristics are usually yielding unclear results. Geno- typic identification by using modern technique which is yielding more accurate results. In this study, ITS region of rDNA was sequenced and phylogenetic tree analysis for Mi- crosporum spp. were observed three clusters of A. otae isolates. When sequencing identi- fies with the reference strains sequence of GenBank Database detected several mutations in multiple locus either by miss matching or genetic gaps. By using Mega 6 software and display toggle conserved sites at the 50% level with different colors of A. otae isolates showed identification of the colors in the nitrogenous bases alignment belong to the same species of the telomorph.